Manufacture of Composite Plastic Pellet Seed Machine Capacity 2.5 Kg/Hour - Alfan Ekajati Latief; Cahyadi Suheri (METAL: Jurnal Sistem Mekanik dan Termal, 2023)
Natural fibers are a material that is easily obtained from nature, both animals and plants. Using natural fibers has been commercially applied in various fields, such as automotive and construction, by mixing PPHI (Polypropylene High Impact) with injection molding and forming plastic pellets. Pellets are extruded with natural pineapple fiber for composite, which requires a composite pellet-making machine, which combines two materials that are not aligned with the material mixing method using a screw inside the barrel, then heated by a heater. The screw pushes the pellets that have been mixed and melted to the die and then dried with water, which will go to the Crusher to be chopped into composite pellet seeds. In this research, a plastic extruder machine with a capacity of 2.5 Kg/hour components used a single screw, heater, die, Crusher, barrel, and hopper, and the time delay in this study is 165º and 180º. The screw rotation is constant at 15 rpm, using a screw diameter of 20 mm x 550 mm and a pitch distance of 1D with an inclination angle of 23º.